2023
DOI: 10.3390/metabo13030330
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Physical Exercise Programs in the Context of NASH Cirrhosis and Liver Transplantation: A Systematic Review

Abstract: In recent years, various physical exercise interventions have been developed with a view to reducing comorbidity and morbidity rates among patients with chronic diseases. Regular physical exercise has been shown to reduce hypertension and mortality in patients with type 2 diabetes. Diabetes and obesity are often associated with the development of nonalcoholic fatty liver disease, which can lead to liver fibrosis and then (in some cases) nonalcoholic steatohepatitis cirrhosis. We searched the literature for pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 125 publications
0
3
0
1
Order By: Relevance
“…On the other hand, a recent expert meeting has gathered strong evidence that regular physical activity plays an important role in preventing NAFLD and improving intermediate clinical outcomes [ 193 ]. Various studies have demonstrated an improvement in NAFLD with personalized physical exercise programs [ 194 ], even in the absence of significant weight loss [ 195 , 196 ], and a reduction of the hepatic venous pressure gradient in cirrhotic patients [ 197 ].…”
Section: Nafld Treatmentmentioning
confidence: 99%
“…On the other hand, a recent expert meeting has gathered strong evidence that regular physical activity plays an important role in preventing NAFLD and improving intermediate clinical outcomes [ 193 ]. Various studies have demonstrated an improvement in NAFLD with personalized physical exercise programs [ 194 ], even in the absence of significant weight loss [ 195 , 196 ], and a reduction of the hepatic venous pressure gradient in cirrhotic patients [ 197 ].…”
Section: Nafld Treatmentmentioning
confidence: 99%
“…In fact, low moderate-vigorous activity has been associated with increased mortality among liver transplant wait-listed patients[ 157 ]. Conversely, exercise interventions have the potential to safely improve exercise capacity, peak oxygen consumption, muscle mass and function, and quality of life, while decreasing the hepatic venous pressure gradient in individuals with cirrhosis[ 158 , 159 ]. This can even reverse the process of frailty in cirrhotic patients.…”
Section: Management Of Frailty In Liver Diseasesmentioning
confidence: 99%
“…Также для коррекции саркопении, слабости в программу реабилитации включают регулярные физические упражнения. В ряде исследований показана польза регулярных аэробных тренировок средней интенсивности [53][54][55]. Физическая активность позволяет увеличить мышечную массу и силу, снизить утомляемость, обеспечивает лучшее качество жизни [56].…”
Section: заболевания билиарной системы и печениunclassified